ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU GUNA MEMINIMISASI BIAYA PERSEDIAAN DENGAN METODE MATERIAL REQUIREMENT PLANNING PADA BATIK MAHKOTA LAWEYAN SURAKARTA - Aji, Kunto; Widajati, Erni; Sumaryanto, Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
This research is an observation. This type of data uses qualitative data and quantitative data. The data source uses primary data and secondary data. Data collection techniques using study documentation. Data analysis uses descriptive method. Data analysis uses descriptive method. The results showed that the application of the Material Requirement Planning method could play a role in minimizing the cost of raw material inventory in Batik Mahkota Laweyan Surakarta, this is indicated by the total cost of raw material inventory using the Economic Order Quantity (EOQ) technique in 2017 of Rp. 3,513,600.00 and in 2018 amounting to Rp. 6,338,400.00, the total cost of raw material inventory using the 2017 Period Order Quantity (POQ) technique is IDR 94,243,200.00 and in 2018 is IDR 114,481,600.00, the total cost of raw material inventory using the Lot For Lot (LFL) technique in 2017 is IDR 61,028,000.00 and in 2018 amounting to Rp 85,880,000.00, and the total cost of inventories of company method raw materials in 2017 is IDR 96,824,000.00 and in 2018 IDR 95,664,800.00. From this comparison it can be seen that the MRP method in the Economic Order Quantity (EOQ) technique produces a total inventory cost in 2017 of IDR 3,513,600.00 and in 2018 of IDR 6,338,400.00 is the result that can save the cost of raw material inventory by 85%, so hypothesis 2 which states that: "the use of the MRP method can streamline the cost of raw material inventory in Batik Mahkota Laweyan Surakarta can optimize production costs", the truth is proven.